The underperformance syndrome: Beyond overtraining - Harnish, C.
When athletes are starting out, training seems so simple: train as much, and as hard as possible and you will get better. This type of strategy is applied to some extent even as we progress in the sport. Long-term improvement requires sufficient stress (overload), some training variation, and adequate recovery. Inadequate recovery from training leads to a failing adaptation - the body fails to compensate for the stress placed on it, leading to reduced performance. In the short-term, this"over-reaching" can lead to significant super compensation. However, continual over-reaching can lead to a vicious cycle of under-performance, or even more severe under-performance, "over-training" - figure 1 provides a graphic depiction of the differences between normal training and super-compensation, over-reaching and overtraining.